All Days 2014
DOI: 10.2118/172220-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Non-damaging Approach to Isolate Open hole Lateral that Allowed Performing Mechanical Descaling in the Non-Monobore Cased Completion: A Case Study in Saudi Arabian Carbonate Reservoir

Abstract: Mechanical descaling of iron sulfide scales in high angle non-monobore or horizontal open hole completion offer multifaceted challenges, especially when the reservoir is depleted. The history of the descaling program in carbonate gas wells in Saudi Arabia dates back to 2007. The program suffered several setbacks with operational complexities like stuck pipe, H2S generation (souring) during chemical dissolution and severe induced damage during reservoir isolation process. The depleted reservoir needs to be isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…It has been found that a fluidic oscillation technology cleaning device (Webb et al 2006, Leal et al 2007, Buali et al 2014) and a high pressure jetting tool with a down-hole motor or turbine with mills (Bolarinwa et al 2012, Mukhliss et al 2014) are effective in removing iron sulfide scales. Current mechanical procedures involve temporary reservoir isolation without formation damage (Buali et al 2014, Mukhliss et al 2014.…”
Section: Scale Removalmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been found that a fluidic oscillation technology cleaning device (Webb et al 2006, Leal et al 2007, Buali et al 2014) and a high pressure jetting tool with a down-hole motor or turbine with mills (Bolarinwa et al 2012, Mukhliss et al 2014) are effective in removing iron sulfide scales. Current mechanical procedures involve temporary reservoir isolation without formation damage (Buali et al 2014, Mukhliss et al 2014.…”
Section: Scale Removalmentioning
confidence: 99%
“…Current mechanical procedures involve temporary reservoir isolation without formation damage (Buali et al 2014, Mukhliss et al 2014. In a severely scaled well, the differential of pressure between the pressure upstream of the choke and downstream of the choke is not changed even though one has decreased the choke of the well.…”
Section: Scale Removalmentioning
confidence: 99%
See 3 more Smart Citations